Expect the unexpected: examining the shaping role of entrepreneurial orientation on causal and effectual decision-making logic during economic crisis. Issue 5 (27th May 2019) - Laskovaia, Anastasiia; Marino, Louis; Shirokova, Galina; Wales, William
ABSTRACT: While many firms operate in dynamic environments, the competitive conditions faced by firms during an economic crisis are especially unstable and turbulent. We examine firm strategic decision-making in this distinctive context and investigate the question of whether causal and effectual logic provide similar paths to performance during such challenging economic times. Further, we examine the potential impact that a firm's level of entrepreneurial orientation (EO) has upon the relationship between managers' predominant decision-making logic and their firm's overall performance in this crisis. To test these relationships, we employ a robust national random sample of 447 Russian small and medium-sized enterprises (SMEs) collected from 2015 to 2016 during a period of economic crisis. Our results indicate that EO plays an important moderating role, shaping the nature of the relationships between managers' decision-making logic and financial performance. Moreover, additional analysis identifies the presence of a non-linear relationship between both logics and the performance of SMEs.